A Novel Conﬁguration-Driven Data Mining Framework for Health and Usage Monitoring Systems - He, David; Bechhoefer, Eric; Al-Kateb, Mohammed; Ma, Jinghua; Joshi, Pradnya; Imadabathuni, Mahindra (IntechOpen, 2011)
None